2020
DOI: 10.1001/jamanetworkopen.2020.9700
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Federal Value-Based Incentive Programs and Health Care–Associated Infection Rates in Safety-Net and Non–Safety-Net Hospitals

Abstract: IMPORTANCE In the US, federal value-based incentive programs are more likely to penalize safety-net institutions than non-safety-net institutions. Whether these programs differentially change the rates of targeted health care-associated infections in safety-net vs non-safety-net hospitals is unknown. OBJECTIVE To assess the association of Hospital-Acquired Condition Reduction Program (HACRP) and Hospital Value-Based Purchasing (HVBP) implementation with changes in rates of targeted health care-associated infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Hsu et al 2020 observed in their study that the healthcare associated infection (HAI) rate of patient demographic characteristics impact of CAUTI on gender has a higher incidence rate 65% as compared to Mutair et al 2019 findings that indicated (57% rate) in the same similar context. 6 , 19 However, the descriptive statistical analysis indicated that mean age of participants was 38.4± 16.8 years and the baseline stages compose 50–60 years (26%) and 30–40 years (20%), which are consistent with previous study conducted by Letica-Kriegel et al 9 The findings of their study indicated risk development of CAUTI increasing with age. The study highlighted the importance of culture of patient safety, which is considered an effective tool to discover areas of improvement.…”
Section: Discussionsupporting
confidence: 85%
“…Hsu et al 2020 observed in their study that the healthcare associated infection (HAI) rate of patient demographic characteristics impact of CAUTI on gender has a higher incidence rate 65% as compared to Mutair et al 2019 findings that indicated (57% rate) in the same similar context. 6 , 19 However, the descriptive statistical analysis indicated that mean age of participants was 38.4± 16.8 years and the baseline stages compose 50–60 years (26%) and 30–40 years (20%), which are consistent with previous study conducted by Letica-Kriegel et al 9 The findings of their study indicated risk development of CAUTI increasing with age. The study highlighted the importance of culture of patient safety, which is considered an effective tool to discover areas of improvement.…”
Section: Discussionsupporting
confidence: 85%
“…For instance, Hsu et al explored the impact of the HVBP and HACRP Programs on health care-related infections among 628 acute care hospitals. Their findings revealed that “… given the persistent disparities in health care–associated infection rates, value-based incentive programs currently function as a disproportionate financial penalty system for safety-net hospitals that provide no measurable population-level benefits” ( 27 ). Similarly, Chaiyachati et al examined a cohort of hospitals to investigate whether racial disparities in hospital readmission rates might have worsened between safety-net and non-safety-net hospitals after participating in the Medicare HRRP Program.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Many studies have found improvements in health care quality in certain cases even though the effects on cost containment appear to have been modest (4,(24)(25)(26). Other studies found no improvement in quality measures and claimed increased costs for certain programs and conditions (24,27). However, these apparently conflicting findings might reflect heterogeneous hospital-level case-complexity where hospitals that care for increasingly complex patients may be less able to reduce costs and improve quality (24).…”
Section: Hospital Vbp E Ectiveness and Implications For Equity And He...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Centers for Medicare and Medicaid (CMS) Hospital Inpatient Quality Reporting Program, for example, requires acute-care hospitals to report central-line-associated bloodstream infections (CLABSIs), catheter-associated urinary tract infections (CAUTIs), a subset of surgical site infections (SSIs), methicillin-resistant Staphylococcus aureus (MRSA) bacteremia, and Clostridioides difficile infections to the Centers for Disease Control and Prevention (CDC) National Healthcare Safety Network (NHSN) and incorporates them into hospital payment program metrics. 13 One important difference between these reportable HAIs and hospital-onset sepsis is that CDC has developed standardized surveillance definitions for reportable HAIs. In contrast, sepsis surveillance has traditionally been conducted using hospital discharge diagnosis codes.…”
mentioning
confidence: 99%